2023
DOI: 10.1021/acs.jafc.2c07059
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-Q-Orbitrap-Based Integrated Lipidomics and Proteomics Reveal Propane-1,2-diol Exposure Accelerating Degradation of Lipids via the Allosteric Effect and Reducing the Nutritional Value of Milk

Abstract: The scandal of detecting the flavoring solvent propane-1,2-diol (PD) in milk has brought a crisis to the trust of consumers in the dairy industry, while its deposition and transformation are still indistinct. Pseudo-targeted lipidomics revealed that PD accelerated the degradation of glycerolipid (33,638.3 ± 28.9 to 104,54.2 ± 28.4 mg kg −1 ), phosphoglyceride (467.4 ± 8.2 to 56.6 ± 4.2 mg kg −1 ), and sphingolipids (11.4 ± 0.3 to 0.7 ± 0.2 mg kg −1 ), which extremely decreased the milk quality. Recoveries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Integrated omics analysis (metabolomics, lipidomics, proteomics) can screen for crucial compounds (metabolites, lipid molecules, and proteins) and propose a coordinated mechanism at different biological layers. Investigated lipidomics and proteomics analysis deeply explore the dynamic changes of lipids and proteins in pasteurized milk contaminated with propane-1,2-diol and reveal propane-1,2-diol exposure accelerating degradation of lipids via the allosteric effect and reducing the nutritional value of milk . UHPLC-Q-Orbitrap HRMS-based integrative metabolomics and proteomics analyses revealed Zanthoxylum bungeanum application alleviates health risks in aflatoxin B1-contaminated goat meat via upregulating glutathione S-transferase, downregulating cytochrome P450 1A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated omics analysis (metabolomics, lipidomics, proteomics) can screen for crucial compounds (metabolites, lipid molecules, and proteins) and propose a coordinated mechanism at different biological layers. Investigated lipidomics and proteomics analysis deeply explore the dynamic changes of lipids and proteins in pasteurized milk contaminated with propane-1,2-diol and reveal propane-1,2-diol exposure accelerating degradation of lipids via the allosteric effect and reducing the nutritional value of milk . UHPLC-Q-Orbitrap HRMS-based integrative metabolomics and proteomics analyses revealed Zanthoxylum bungeanum application alleviates health risks in aflatoxin B1-contaminated goat meat via upregulating glutathione S-transferase, downregulating cytochrome P450 1A .…”
Section: Introductionmentioning
confidence: 99%
“…Investigated lipidomics and proteomics analysis deeply explore the dynamic changes of lipids and proteins in pasteurized milk contaminated with propane-1,2-diol and reveal propane-1,2-diol exposure accelerating degradation of lipids via the allosteric effect and reducing the nutritional value of milk. 20 UHPLC-Q-Orbitrap HRMS-based integrative metabolomics and proteomics analyses revealed Zanthoxylum bungeanum application alleviates health risks in aflatoxin B1-contaminated goat meat via upregulating glutathione S-transferase, downregulating cytochrome P450 1A. 21 The molecular mechanism of propylene glycol-induced lipolysis of the biosynthesis pathway in ultrahigh temperature milk was unraveled combined UHPLC-Q-Orbitrap HRMS-based metabolomics and proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…Animal-sourced milk is the primary nutritional source for the development of infants after weaning, and the recommended age for neonates to consume animal-derived milk is typically 12 months to prevent iron-deficiency anemia . Increasing evidence in literature indicate that goat milk can be considered as a high-quality ingredient for infant complementary foods and follow-on formula due to its potential health benefits, specifically including improvements in gastrointestinal disorders, hypo allergenicity, promoting the absorption of iron and copper ions, and elevating the levels of vitamin A, thiamine, Ca, niacin, cholesterol and riboflavin. , In addition, goat milk proteins are a vital source of bioactive peptides and provide essential amino acids for the growth and development of infants. , A small number of peptides can be naturally present in goat milk, while the majority of them are generated during gastrointestinal digestion. , It had been reported that foods with different physicochemical properties such as viscosity, microstructure, and various enzymatic hydrolysis conditions lead to the differences in the digestion; however, the relevance of active peptides to infant health depends on whether they are released during gastrointestinal digestion and whether they survive to reach their sites of activity . Elevating the digestibility of protein in the gastrointestinal tract is the crux to promote the release of bioactive peptides and improve the bioaccessibility and bioavailability of goat milk, which warrants further investigation on its potential functions in the health and development of infants and young children.…”
Section: Introductionmentioning
confidence: 99%
“…Current research focuses on the identification of the peptides in goat milk and the improvement of the immune effect of postbiotic supplementation on organisms, while the effect of postbiotics on bioactive peptide release in goat milk during gastrointestinal digestion is still not clear . In this study, ultra-high performance liquid chromatography-quadrupole-Orbitrap (UHPLC-Q-Orbitrap)-based spatial omics combined with vDIA acquisition model and the unsupervised variational autoencoders is applied to profile the molecular mechanism of postbiotic supplementation- induced release of bioactive peptides in goat milk during gastrointestinal digestion, which establishes a critical groundwork and provides evidence for the clinical application of postbiotics in infant complementary foods (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation